2015
DOI: 10.1016/j.ejmech.2015.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Small lipidated anti-obesity compounds derived from neuromedin U

Abstract: A small library of truncated/lipid-conjugated neuromedin U (NmU) analogs was synthesized and tested in vitro using an intracellular calcium signaling assay. The selected, most active analogs were then tested in vivo, and showed potent anorexigenic effects in a diet-induced obese (DIO) mouse model. The most promising compound, NM4-C16 was effective in a once-weekly-dose regimen. Collectively, our findings suggest that short, lipidated analogs of NmU are suitable leads for the development of novel anti-obesity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 104 publications
0
17
0
Order By: Relevance
“…Next, the peptide was cleaved further at the same position Previously, the stability of some NMU-based molecules was already reported in literature. Lipidation of NMU-8 markedly increased its half-life in mouse plasma as compared to hNMU [21]. Moreover, when the effect on proteolytic stability was studied of molecules without high molecular carriers, improved resistance towards degradation was observed as well.…”
Section: In Vitro Plasma Stabilitymentioning
confidence: 94%
See 1 more Smart Citation
“…Next, the peptide was cleaved further at the same position Previously, the stability of some NMU-based molecules was already reported in literature. Lipidation of NMU-8 markedly increased its half-life in mouse plasma as compared to hNMU [21]. Moreover, when the effect on proteolytic stability was studied of molecules without high molecular carriers, improved resistance towards degradation was observed as well.…”
Section: In Vitro Plasma Stabilitymentioning
confidence: 94%
“…Additionally, other novel analogs based on the truncated form of NMU, such as small lipidated NMUanalogs [21] and PEGylated NMU-8 [22], were already described to have potent anorectic and antiobesity effects. Several molecules based on the long version of NMU were synthesized as well, including a NMU-25 conjugate with human serum albumin [23], a PEGylated NMU-25 derivative [24] and lipidated NMU-25 analogs [25].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Obesity has turned into one of the most serious health problems in the current century and it is believed to elevate the probability of heart disease, type-2 diabetes, obstructive sleep apnea, certain types of cancer, and osteoarthritis, among others (Micewicz et al, 2015). There has thus been a great deal of interest in anti-obesity drugs with satiating and appetite suppressant effects; however, the use of these drugs is limited due to their adverse effects such as depression and cardiovascular risks (Ziauddeen and Fletcher, 2013).…”
Section: Anti-obesitymentioning
confidence: 99%
“…More recently, (Micewicz et al, 2015) revealed that NM4-C 16 , a truncated/lipid-conjugated neuromedin U (NmU) analog, has strong appetite suppressing effects in a diet-induced obese (DIO) mouse model; it is noteworthy that Neuromedin U (NmU) is an endogenous peptide with various physiological effects.…”
Section: Anti-obesitymentioning
confidence: 99%
“…During digestion, BP must cross the gastrointestinal barrier and survive enzyme degradation in order to have a positive health effect [ 47 ]. Depending on the sequence of the amino acid sequence, BP render many functional, physiological, and therapeutic properties, including antihypertensive [ 48 ], antioxidant [ 48 , 49 ], anti-obesity [ 50 ], antifungal, antiviral, immunomodulatory [ 51 ], antimicrobial [ 51 , 52 ], anticoagulant [ 53 ], anti-inflammatory [ 54 ], antidiabetic, iron- and calcium-binding activities [ 55 ], antiproliferative [ 56 ] and chelating effects [ 57 ]. They also account for the taste of food and the inhibition of enzymes involved in developing diseases.…”
Section: Antioxidative Peptidesmentioning
confidence: 99%